ANALISA TEMBAK DI TEMPAT YANG DILAKUKAN OLEH ANGGOTA POLISI TERHADAP PELAKU KRIMINAL DALAM UPAYA PENEGAKAN HUKUM PIDANA - Dedi Kurniawan Susilo; Abdul Bari Azed; Sarbaini Sarbaini (Legalitas: Jurnal Hukum, 2021)
The police shoots on the spot against Criminals in the Effort of Criminal Law Enforcement is the last step, however after close attention, the term "shoot on the spot" is not explicitly found in the laws governing the Police. So that research is carried out in the form of a thesis with the following objectives: 1) understanding and analyzing the shooting arrangements carried out by members of the police against criminals in the effort to enforce criminal law according to Indonesian legislation; 2) understand and analyze the legal protection of police officers who shoot on the spot in law enforcement and the exercise of the authority to fire on the spot can avoid acts of abuse and arrogance of power by members of the National Police. The research method used is normative juridical research. Based on the results of the research: 1) Arrangement of shooting at the spot by members of the police against criminals in an effort to enforce criminal law is a right of discretion based on statutory regulations, namely the Criminal Code, Law Number 2 of 2002 concerning the State Police. Republic of Indonesia, Law Number 39 of 1999 concerning Human Rights, Regulation of the Head of the Republic of Indonesia Police Number 1 of 2009 concerning the Use of Force in Police Actions, Regulation of the Chief of Police of the Republic of Indonesia Number 8 of 2009 concerning Implementation of Human Rights Principles and Standards in the Implementation of Republican Police Duties Indonesia. 2) Legal protection for police officers who shoot on the spot in law enforcement and exercising the authority to fire on the spot can avoid acts of abuse and arrogance of power by members of the National Police, namely avoiding police members from acting contrary to human rights, and not only based on discretionary rights. which is owned by the Police but is given a special legal umbrella in the execution of shooting on the spot against criminals who violate the SOPs in law enforcement at the police level in creating ready-to-use Police members who have motivation, dedication, and skills in carrying out their duties, can distinguish which ones become authority and rights in taking action, as well as creating Police who cling to TRI BRATA and CATUR PRASTYA as life guidelines and guidelines